2010
DOI: 10.1007/s12264-010-9142-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effects of insulin-like growth factor-1 on the expression of sensory neuropeptide mRNAs in cultured dorsal root ganglion neurons with excitotoxicity induced by glutamate

Abstract: IGF-1 may exert neuroprotective effects on DRG neurons against Glu-induced excitotoxicity, probably through regulating the expression levels of PPT and CGRP mRNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…SP release and SP levels in primary sensory neurons are infl uenced by many factors [17][18][19][20] . A previous study has shown that the α1-adrenoreceptor agonist phenylephrine causes the release of SP from terminals of CAP-sensitive sensory neurons in the lumbar enlargement of the dorsal spinal cord and urinary bladder [5] .…”
Section: Introductionmentioning
confidence: 99%
“…SP release and SP levels in primary sensory neurons are infl uenced by many factors [17][18][19][20] . A previous study has shown that the α1-adrenoreceptor agonist phenylephrine causes the release of SP from terminals of CAP-sensitive sensory neurons in the lumbar enlargement of the dorsal spinal cord and urinary bladder [5] .…”
Section: Introductionmentioning
confidence: 99%